Coastal eceanographic studies off Port Dickson - Law, Ah Theem; Mohd Shazili, Noor Azhar; Liew, Hock Chark; Shamsuddin, Lokman (1988)
This paper summaries the preliminary results from one and a half years of study on the chemical,physical and biological properties of the Ports Dickson coastal waters. The study area covered the entire coast of Port Dickson and extended out to approximately 5km from the coast. The salinity,temperature,pH and dissolved oxygen levels were not significantly different throughout the water column nor among different stations in the study area. This reflects Port Dickson coastal water is well mixed within this area. The water was rich in nutrients (orthophosphate,nitrate and ammonium),high in dissolved oxygen and low in heavy metals. High fecal coliform counts were found in near-shore waters,however coliforms were undetectable in the coastal waters and coastal sediments. Petroleum hydrocarbon level in water seemed to be increasing from July 1986 to August 1987. However,no significant increases were all below the maximum safe permissible level for human consumption. The dominant species of phytoplankton detected in water were diatoms. There was about 10% of commercially important fish larvae (in number) in the fish larval sample.